Networked Professional Development: Issues for recipients and providers - Bowskill, Nicholas; Foster, Jonathan; Lally, Vic; McConell, David (Proceedings of the International Conference on Networked Learning, 2000)
The Computer Based Collaborative Group. Work (CBCGW) Project is based in the Department of Educational Studies at Sheffield University. The aim of the project is to help raise awareness and to support the development of practice amongst those interested or involved in collaborative networked teaching and learning. The Project team has delivered a range of different resources and activities to different audiences within Higher Education. This support, labelled as the Rich Professional Development Environment (RPDE). is one strand of the project. As part of the RPDE this paper describes an online workshop for academics and a support initiative for staff developers. Finally some consideration is given to our collaborative networked teaching practice as another aspect of networked group learning and an emerging form of practice.